3D interconnected macro-mesoporous electrode with self-assembled NiO nanodots for high-performance supercapacitor-like Li-ion battery. (April 2016) - Zheng, Xianfeng; Wang, Hongen; Wang, Chao; Deng, Zhao; Chen, Lihua; Li, Yu; Hasan, Tawfique; Su, Bao-Lian
Abstract: We report a binder-free three-dimensional (3D) macro-mesoporous electrode architecture via self-assembly of 3 nm NiO nanodots on macroporous nickel foam for high performance supercapacitor-like lithium battery. This electrode architecture provides a hierarchically 3D macro-mesoporous electrolyte-filled network that simultaneously enables rapid ion transfer and ultra-short solid-phase ion diffusion. Benefitting from the structural superiority owing to the interconnected porous hierarchy, the electrode exhibits supercapacitor-like high rate capabilities with high lithium battery capacities during the discharge-charge process: a very high capacity of 518 mA h g −1 at an ultrahigh current density of 50 A g −1 . It exceeds at least ~10 times than that of the state-of-the-art graphite anode, which shows only ~50 mA h g −1 at ~2 to 3 A g −1 as anode for Li-ion batteries. The preparation method of 3D interconnected hierarchically macro-mesoporous electrode presented here can provide an efficient new binder-free electrode technique towards the development of high-performance supercapacitor-like Li-ion batteries. Graphical abstract: A binder-free 3D interconnected macro-mesoporous NiO electrode for rapid ion transfer and ultra-short solid-phase ion diffusion has been developed via self-assembly of 3 nm NiO nanodots on macroporous nickel foam. The electrode enables Li-ion storage battery working with supercapacitor rate capability while maintaining high battery capacity. This work described here highlights a new approach to fabricate high-performance electrochemical energy storage devices with both high power as well as energy density. Highlights: High-performance supercapacitor-like Li-ion battery concept has been proposed. 3 nm NiO nanodots have been deposited on macroporous nickel foam by self-assembly method. Binder-free three-dimensional (3D) hierarchically macro-mesoporous electrodes have been prepared. This electrode architecture simultaneously enables rapid ion transfer and ultra-short solid-phase ion diffusion. The electrode exhibits supercapacitor-like high rate capabilities with high lithium battery capacities.